A REVIEW ON SUPRAMOLECULAR CHEMISTRY IN DRUG DESIGN AND FORMULATION RESEARCH - Vepuri, Suresh B; Anbazhagan, S.; Divya, D.; Padmini, D. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Supramolecular chemistry, other way called as intermolecular chemistry disclose the relationship of molecules with environment. It exploits while exposing the physicochemical phenomina that happens when two like or unlike molecules/ions/systems contact each other. Drug action involve the target recognition process and response triggered by the intermolecular complex of drug and target. Drug design therefore require in depth study of intermolecular forces that exist between drug and target. Formulation of the drug or Active Pharmaceutical Ingredient (API) is also regulated by these forces. Compatibility and incompatibility in formulations are nothing but of the effect of the intermolecular forces on physical behavior of systems. Therefore review of intermolecular chemistry in general and its role particularly in pharmaceutical research is presented here for the benefit of the students and research scholars who aspire to work on interdisciplinary projects in the field of pharmacy. Key words: intermolecular forces, hydrogen bond, drug design, active pharmaceutical ingredient (API), crystal.